The role of refugee established churches in the lives of forced migrants: a case study of Word of Life assembly in Yeoville, Johannesburg - Nzayabino, Vedaste (My University, 2006)
‘Making things our own’. This is one of the ultimate goals pursued in establishing churches within refugee communities. The refugee church has become both a channel of material support and spiritual factory where social and emotional fabrics are strongly rewoven among people linked together by a common culture and shared experience. This is a qualitative case-study of the Word of Life Assembly (WOLA), one of the independent churches established by forced migrants in Yeoville, Johannesburg. Established by a Congolese pastor, the church counts a total of about 450 members, mostly refugees (about 98%), predominantly from the Democratic Republic of Congo (more than 95%). The study seeks to explore the role of the church in the lives of refugees, and determine the ways forced migrants understand this role. More importantly, it was found that WOLA has been able to integrate refugees who could not otherwise integrate in local or domestic churches in Johannesburg. Language and spiritual problems have been identified as the major barriers to integration. In this respect, the study has revealed four levels of integration within WOLA church; that is, integration of a refugee into a refugee community, religious integration, and cultural integration. The fourth level of integration consists of integration of the refugee church itself. In this regard, it was revealed that, as far as refugee church is concerned, not only church members are to integrate into host community and/or churches, but the [refugee] church itself – labelled thus as a ‘foreign’ entity – is to seek its own integration into and approval from the South African community in general, and host faith-based institutions in particular. Moreover, the study revealed that, in an attempt to meet the diverse needs of its members, WOLA offers a wide range of special services and activities, notably material and social assistance, and pastoral counseling. Finally, WOLA has become a strategic place where religious and socio-cultural identities are easily built and maintained among members, and where social networks are interwoven among refugees themselves, and between refugees and their country of origin.
Nzayabino, Vedaste. 0419340w. Research report submitted to Faculty of Arts in partial fulfilment of the requirements for the degree of Master of Arts. Johannesburg 2005
Keywords: refugee church; wola; Word of Life Assembly; integration; socio-cultural identities; cultural